Loricrin and Cytokeratin Disorganisation in Severe Forms of Periodontitis - Raisa Queiroz Catunda; Karen Ka-yan Ho; Srushti Patel; Christopher Bryant Roy; Maria Alexiou; Liran Levin; Benjamin J. Ulrich; Mark H. Kaplan; Maria Febbraio (International Dental Journal, 2023)
Objective: The aim of this research was to investigate the role of the cornified epithelium, the outermost layer of the oral mucosa, engineered to prevent water loss and microorganism invasion, in severe forms of periodontitis (stage III or IV, grade C). Methods: Porphyromonas gingivalis, a major periodontal disease pathogen, can affect cornified epithelial protein expression through chronic activation of signal transducer and activator of transcription 6 (Stat6). We used a mouse model, Stat6VT, that mimics this to determine the effects of barrier defect on P gingivalis–induced inflammation, bone loss, and cornified epithelial protein expression, and compared histologic and immunohistologic findings with tissues obtained from human controls and patients with stage III and IV, grade C disease. Alveolar bone loss in mice was assessed using micro-computerised tomography, and soft tissue morphology was qualitatively and semi-quantitatively assessed by histologic examination for several proteins, including loricrin, filaggrin, cytokeratin 1, cytokeratin 14, a proliferation marker, a pan-leukocyte marker, as well as morphologic signs of inflammation. Relative cytokine levels were measured in mouse plasma by cytokine array. Results: In the tissues from patients with periodontal disease, there were greater signs of inflammation (rete pegs, clear cells, inflammatory infiltrates) and a decrease and broadening of expression of loricrin and cytokeratin 1. Cytokeratin 14 expression was also broader and decreased in stage IV. P gingivalis–infected Stat6VT mice showed greater alveolar bone loss in 9 out of 16 examined sites, and similar patterns of disruption to human patients in expression of loricrin and cytokeratins 1 and 14. There were also increased numbers of leukocytes, decreased proliferation, and greater signs of inflammation compared with P gingivalis–infected control mice. Conclusions: Our study provides evidence that changes in epithelial organisation can exacerbate the effects of P gingivalis infection, with similarities to the most severe forms of human periodontitis.